2014
DOI: 10.1007/s40519-014-0137-0
|View full text |Cite
|
Sign up to set email alerts
|

Eating habits and dietary patterns in children with autism

Abstract: The children with autism have feeding problems such as chewing, preference for the same food that often are responsible for the nutrient imbalance. In this study, we have analyzed the differences in food consumption (food frequency) and eating behavior (CEBI test) between children with autism and their typically developing peers. A statistically significant difference was observed between the two groups for the consumption of milk, yogurt, pulses, rice, and fruit juices (p ≤ 0,005). We observed a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 19 publications
6
30
0
9
Order By: Relevance
“…Previous researchers [ 4 ] [ 39 ] [ 40 ] [ 41 ] [ 42 ] showed that autistic children are very sensitive to bitter taste leading to refusal of certain foods and it could be the potential reason for reduced intake of vegetables in par with our study where 68.9% of the children rejected having vegetables. In contrast, According to Diolordi L et al, [ 39 ] fruits are preferred by the autistic children may be because of its texture and sweet taste wherein our study, 78.7% of the children preferred having fruits. About dental caries, previous researchers [ 13 ] analysed that fruits/vegetables are having a snack replacing the sugar or sweet reduced dental caries.…”
Section: Discussionsupporting
confidence: 67%
“…Previous researchers [ 4 ] [ 39 ] [ 40 ] [ 41 ] [ 42 ] showed that autistic children are very sensitive to bitter taste leading to refusal of certain foods and it could be the potential reason for reduced intake of vegetables in par with our study where 68.9% of the children rejected having vegetables. In contrast, According to Diolordi L et al, [ 39 ] fruits are preferred by the autistic children may be because of its texture and sweet taste wherein our study, 78.7% of the children preferred having fruits. About dental caries, previous researchers [ 13 ] analysed that fruits/vegetables are having a snack replacing the sugar or sweet reduced dental caries.…”
Section: Discussionsupporting
confidence: 67%
“…Second, dietary intake and absorption may influence blood glutamate levels. Particular eating habits, dietary patterns [ 34 ] and functional gastrointestinal abnormalities [ 35 ] have been observed in ASD. These factors may contribute to the altered blood glutamate levels in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Permasalahan tersebut dialami oleh 46-89% anak ASD. 9,10 Pemilihan makanan pada anak ASD biasanya berdasarkan jenis, tekstur, suhu dan bau tertentu. [11][12][13] Perilaku pemilihan makan ini dapat menggambarkan suatu pola pembatasan makanan yang dapat berlanjut dan berperan dalam gangguan perilaku makan saat dewasa.…”
Section: Pendahuluanunclassified
“…33 Beberapa penelitian melaporkan bahwa penerapan diet bebas gluten dan kasein dapat meningkatkan kualitas tidur dan menurunkan perilaku agresif. 10 Gluten dan kasein yang diasup anak ASD tidak tercerna sempurna dan menyebabkan aktifnya senyawa jenis pre-opioid (eksorfin: casomorfin dan gluteomorfin) dari gluten dan kasein. Eksorfin ini diserap dan masuk aliran darah serta mengikat pada reseptor opioid otak, sehingga berdampak pada kekurangan tidur, ketidakfokusan, dan sifat agresif, serta menyakiti diri sendiri.…”
Section: Bahan Dan Metodeunclassified